Review of Counseling Female Offenders and Victims: A Strengths-Restorative Approach. Katherine Van Wormer. Reviewed by Elizabeth C. Pomeroy - Pomeroy, Elizabeth C. (2002)
Maluccio, A.N. & Daly, J. (2000). Family group conferencing as good child welfare practice. In Gail Buford & Joe Hudson (Eds.), Family Group Conferencing: New Directions in Community- Centered Child and Family Practice (pp. 66-71). New York: Aldine DeGruyter